2009
DOI: 10.1016/j.juro.2009.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Early Valve Ablation Can Decrease the Incidence of Bladder Dysfunction in Boys With Posterior Urethral Valves

Abstract: Neonatal valve ablation would protect the bladder and allow normal cycling, which helps in bladder healing. This underscores the importance of routine prenatal screening and early intervention at a specialized center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
0
20
1
Order By: Relevance
“…Current therapies include percutaneous vesico-amniotic shunting [5,6,8,9,13,16,19] and in utero fetoscopic ablation of valves by percutaneous fetal cystoscopy that allows laser valve ablation [12,15] and mechanical disruption of posterior urethral valves [3,4,8,17,18,20].…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies include percutaneous vesico-amniotic shunting [5,6,8,9,13,16,19] and in utero fetoscopic ablation of valves by percutaneous fetal cystoscopy that allows laser valve ablation [12,15] and mechanical disruption of posterior urethral valves [3,4,8,17,18,20].…”
Section: Discussionmentioning
confidence: 99%
“…The potential risk of valve remnants causing a degree of persistent outflow impairment, and the longterm consequences for bladder and/or renal function that this may have, stir us into wanting to confirm or achieve complete resection of PUV in the first few months. So far, early diagnosis and management of PUV have been shown to benefit long-term renal function [12] and bladder function in the short term [13]. Kousidis et al [12] observed better renal function in the second decade of life for prenatally detected PUV than for those presenting clinically, many following urinary infection, later in life, indicating long-term benefit from early nephrological and urological care, including the prompt relief of bladder outflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Kousidis et al [12] observed better renal function in the second decade of life for prenatally detected PUV than for those presenting clinically, many following urinary infection, later in life, indicating long-term benefit from early nephrological and urological care, including the prompt relief of bladder outflow obstruction. Youssif et al [13] noted better bladder capacity, compliance and stability in boys at the age of 3 years whose valves were resected in the neonatal period as compared to those whose valves were ablated after 1 year of age. Particularly in early infancy, there is no reliable alternative to endoscopy for confirming complete valve resection.…”
Section: Discussionmentioning
confidence: 99%
“…In a series reported that urologic symptoms included VUR and renal failure were shown in 33% and 14% of children with spinal dysraphism after a long term follow-up (Silveri, Capitanucci et al 1997). The non-neurogenic disorders affect the voiding function in children including posterior urethral valves, Hinmain's syndrome, prune belly syndrome (Chaichanamong Kol, Ikeda et al 2008;Youssif, Dawood et al 2009;Routh, Huang et al 2010), which are highly associated with febrile UTI and chronic renal failure (Őborn and Herthelius 2010). The management of UTIs in children associated with voiding dysfunction is complex, the underlying disorders should be appraised when the symptoms are initially presented.…”
Section: Voiding Disordersmentioning
confidence: 99%